Kajian Awal : Prediksi Kabut Berdasarkan Data Observasi di Wilayah Bandara Zainuddin Abdul Madjid - Dewita, Anggi; Alfiandy, Solih (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2024)
The reduction in visibility due to wet particles (fog and mist) is a phenomenon that can occur at Zainuddin Abdul Madjid Airport (ZAM). This event is quite difficult to predict using NWP models because the physical processes involved in its formation are very complex. This study aims to determine the threshold parameters that can be used as a forecasting guide to predict the occurrence of fog. The data used is from January 2024, with parameters assessed from METAR, AWOS, and Fklim71, including wind speed, temperature, dew point, cloud cover, and maximum temperature. The threshold values for each parameter will be determined and tested using a dichotomous verification method to obtain the accuracy value. Based on the analysis, fog in January 2024 formed early in the morning if there was precipitation during the afternoon, with the average wind speed at night being < 1 knot, the temperature difference between maximum temperature and air temperature after sunset being > 4.5°C, and the dew point depression at 17:00 UTC being below 1°C. In January 2024, a dichotomous verification was carried out, and the result showed an accuracy of 87%. Forecasting using this method is not 100% accurate.